Gambaran Penggunaan Antıhıpertensı pada Pasıen ST- Elevatıon Myocardıal Infractıon - Khofifah aulia; Irma Novrianti; Jufri Ubrusun (Politeknik Kaltara, 2022)
ST-Elevation Myocardial Infraction (STEMI) is caused by several factors, mainly due to cardiovascular disorders. There are several complaints from STEMI, such as chest pain, elevated enzymes, and ST elevation on electrocardiogram examination. One of the major factors in the occurrence of STEMI is hypertension. The more severe the hypertension condition will slowly damage the blood vessel walls causing swelling, which leads to STEMI. This study aimed to see the use of antihypertensives in stemmy patients who were using fibrinolytic therapy. This research method is descriptive retrospective by looking at the medical records of STEMI patients who received antihypertensive treatment at the Emergency Room (ER) and were hospitalized at Tarakan City